The Quarries of Meroe, Sudan : Part 1 - Text - Thilo Rehren (6784496) (2018)
About Part 1 A team of international researchers present their research on all aspects of quarrying: history, geology, quarrying technique, graffiti in quarries, Meroitic and Greek inscriptions in quarries, as well as the petrography of Nubian sandstone. A final chapter deals with the challenges of surveying quarries in the desert. All articles have extensive Arabic summaries. Map A map in A0 format of the wider study area, with individual quarry locations marked. PDF - 25 MB. Video This two-part set is accompanied by five short educational and illustrative slideshows in English and Arabic about the authors’ work on the sandstone quarries around Meroe. The highlight is a 5-minute aerial and underground ‘fly-through’ video presenting quarry Q41, the largest and most impressive of the gallery quarries in the study area, available in 2D or 3D. All videos are available here: https://www.youtube.com/playlist?list=PL7-ic31cMSbvWosaClqx-qHJYtYWraVgB. Acknowledgement This publication and the associated videos were made possible by NPRP grant 5-879-6-025 from the Qatar National Research Fund (a member of Qatar Foundation). The statements made herein are solely the responsibility of the author(s). Other Information Editors: Brigitte Cech, Thilo Rehren and Abdelrahman Ali Mohamed License: https://creativecommons.org/licenses/by/4.0 See book on publisher's website: https://doi.org/10.5339/uclq.2018.9789927118876